The influence of social media on religious identity politics among Indonesian millennial generation - Cucu Nur Hayati; A. Bakir Ihsan; Muhammad Farras Shaka (Universitas Trunojoyo Madura, 2022)
The millennial generation and social media are like two sides of a coin. Social media has become an inherent identity of the main characteristics of the millennial generation, who are adaptive, innovative, and pragmatic. Under these conditions, this research studies whether social media disproportionately impacts the behaviours of the millennial generation, especially in the era of the Covid-19 pandemic, which demands online interactions. Through qualitative methods, this article is based on the analysis of documents related to religious identity politics on social media and is strengthened by in-depth interviews. From data analysis and interviews, it is evident that the millennial generation accesses social media more than just as a medium of entertainment. It is also driven by the interests of communication and seeking answers to problems of life. Even if the millennial generation accesses platforms that lead to religious identity politics, it is more driven by a momentary curiosity about the issues that are present in their minds, except for those who have been indoctrinated by an exclusive religious understanding from the start and place politics as an inseparable part of their religious identity.